2021
DOI: 10.1155/2021/9977001
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Interfering with pak4 Protein Expression Affects Osteosarcoma Cell Proliferation and Migration

Abstract: Purpose. A number of studies have discovered various roles of PAK4 in human tumors, including osteosarcoma. However, the exact role of PAK4 in osteosarcoma and its mechanism have yet to be determined. Therefore, this study focused on interrogating the PAK4 effect on the proliferation and migration ability of osteosarcoma and its underlying mechanisms. Materials and Methods. Western blot and QRT-PCR were utilized to quantify the PAK4 relative protein and mRNA levels. To measure cellular viability and mobility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Motion trajectories of U2-OS and MG-63 cells were tracked and imaged using a Holomonitor ® M4 microscope [ 15 ]. Open the microscope component of the Holomonitor ® M4 system and place it in the CO 2 incubator overnight to improve the stability of each parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Motion trajectories of U2-OS and MG-63 cells were tracked and imaged using a Holomonitor ® M4 microscope [ 15 ]. Open the microscope component of the Holomonitor ® M4 system and place it in the CO 2 incubator overnight to improve the stability of each parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, more and more evidences suggested that PAK4 might be an ideal target for treat certain cancers ( Santiago-Gómez et al, 2019 ; Wang F et al, 2019 ; Dasgupta et al, 2021 ). Inhibition of PAK4 was found to attenuate cancer cell migration and invasion, and suppress growth of diverse tumors in vivo ( Guo et al, 2020 ; Fu et al, 2021 ). Furthermore, PAK4 was also found as an important regulator of tumor immunity ( Nasmall Yi et al, 2021 ), thus opening a novel landscape for PAK4-related therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%